2015
DOI: 10.1016/j.rbmo.2014.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Zinc protects sperm from being damaged by reactive oxygen species in assisted reproduction techniques

Abstract: The aim of this study was to explore the effect of zinc on hydrogen peroxide-induced sperm damage in assisted reproduction techniques. First, sperms were selected from semen samples of 20 healthy men prepared by density gradient centrifugation. Selected sperm were treated with either 0.001% H(2)O(2), 12.5 nM ZnCL(2), 0.001% H(2)O(2) + 12.5 nM ZnCL(2) or 0.9% NaCl(2) (control). After this treatment, the motility, viability, membrane integrity and DNA fragmentation of sperms in each group were analysed by Goodli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…For example, the MRE11 complex is an important source of stress relief, being a key component of DNA repair [ 107 ]. The most studied antioxidants are ascorbic acid (Vitamin C), tocopherols (Vitamin E), and carotenoids (Vitamin A), but enzymes, as well as Vitamin B complex, glutathione, pantothenic acid, coenzyme Q10, and carnitine, and micronutrients such as zinc, selenium, and copper seem to be also important [ 29 , 108 , 109 ]. However, only low quality evidence suggests that antioxidant supplementation in subfertile males may improve clinical pregnancy rates [ 5 ] and in pregnant women there were no changes in smoking induced OS in relation to vitamin supplement intake [ 110 ].…”
Section: Intervention Optionsmentioning
confidence: 99%
“…For example, the MRE11 complex is an important source of stress relief, being a key component of DNA repair [ 107 ]. The most studied antioxidants are ascorbic acid (Vitamin C), tocopherols (Vitamin E), and carotenoids (Vitamin A), but enzymes, as well as Vitamin B complex, glutathione, pantothenic acid, coenzyme Q10, and carnitine, and micronutrients such as zinc, selenium, and copper seem to be also important [ 29 , 108 , 109 ]. However, only low quality evidence suggests that antioxidant supplementation in subfertile males may improve clinical pregnancy rates [ 5 ] and in pregnant women there were no changes in smoking induced OS in relation to vitamin supplement intake [ 110 ].…”
Section: Intervention Optionsmentioning
confidence: 99%
“…The addition of antioxidants, such as zinc, in the freezing medium to improve the fertility capacity and preserve the sperm from oxidative damage is becoming increasingly widespread [ 136 , 137 ]. Studies revealed that, after incubation with hydrogen peroxide, the DNA fragmentation percentage in spermatozoa was increased, and the effect was reversed by zinc supplementation to the medium [ 138 ].…”
Section: Zinc and Fertilitymentioning
confidence: 99%
“…Recent studies demonstrated the beneficial effects of zinc addition to human ejaculate before cryopreservation on sperm viability and motility after thawing [ 138 , 139 ]. The freezing of human sperm in the presence of 50-µM zinc revealed a 26–184% increase in the number of motile sperm after thawing and a 130% increase in the percentage of progressive motility compared to a control without zinc [ 139 ].…”
Section: Zinc and Fertilitymentioning
confidence: 99%
“…Several studies on Zinc and its compounds have been published over the past decade the latest available literature about the embryo development on equine [24], antioxidant and antiinfl ammatory effects on testicular damage in rats [25] [19,[26][27][28][29][30][31][32], protection of sperm against reactive oxygen species in men [33], male sex hormones and semen quality in rats [23], toxic effect on male reproduction system of different species (e.g. [34][35][36].…”
Section: Introductionmentioning
confidence: 99%